56.1: Invited Paper: Research on Measuring Methods of Immersion for Virtual Display Based on Neurocomputing. (26th August 2021) - Qiao, Bo; Pei, Guanxiong; Pan, Yang; Li, Taihao; Yao, Shuai; Fang, Shishi
Abstract : Immersion is an important parameter to characterize the performance of VR in interaction. At present, the evaluation of immersion is basically based on the measurement of optical properties, image quality and other indirect indicators, without considering the actual feelings of people. In this study, we proposed a measuring methods of immersion for virtual display based on neurocomputing method. By comparing with self‐report method, the consistency index was at a relatively high level, which indicates that EEG‐based neurocomputing offers an option to evaluate the immersion of virtual display.